Specialized pharmaceutical care in social health centers in the times of COVID-19 - Juan F. Peris-Martí; Patricia Bravo-José; Carmen Sáez-Lleó; Elia Fernández-Villalba (Farmacia Hospitalaria)
The COVID-19 pandemic is having a devastating effect on the nursing homes for dependent older people. The difficulty of management of this crisis is aggravated by the frailty of the people served and by the specific characteristics of the care area, mainly the fact of not being integrated into the health system. The objective of this work is to describe the pharmaceutical care developed by a hospital pharmacy service established in a nursing home and, from a more global perspective, analyze the strengths and weaknesses found from the various experiences of hospital pharmacy in all spanish autonomous communities to deal with this pandemic. Specialized pharmaceutical care has provided rigor in the validation and treatments review processes from a comprehensive perspective, maximizing safety and collaborating in the establishment of the therapeutic intensity degree most appropriate to the individual situation, has ensured the availability of all necessary medications, has collaborated in the acquisition and management of personal protective equipment, has been able to adapt the dispensation processes to the internal nursing homes sectorization and has facilitated the coordination between the nursing home and the health system. It is clear that the crisis casued by COVID- 19 has put relevance of the need to integrate the social-health level into the health system. And also, the contribution of specialized pharmaceutical care in improving healthcare coverage and coordination with health services has highlighted the urgency of developing the current legislation, prioritizing the establishment of pharmacy services able to provid specialized and specific care for this area, so that it meets healthcare needs and is integrated into the health system.